BERITA POLITIK DAN PEMERINTAHAN KALEIDOSKOP 2015 KOMPAS.COM: PERSPEKTIF ANALISIS WACANA KRITIS FAIRCLOUGH - Kacung (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This study was carried out with the purpose to explain the using of the grammatical in the news of politics and Government Kaleidoscope 2015 Kompas.com. The studydata was sourced from the linguistic phenomenon in the grammatical form in the news of political and Government Kaleidoscope 2015 Kompas.com. The data was collected by the documentation method. Data analysis was done sequentially, data collection, reduction, rendering, and conclution. The results of this study showed that the using of the grammatical, the transitive Sentence generally was used to accentuate the perpetrator’s actions. Saw primarily done to the offender who break the law, norms, and ethics. The intransitif sentence was used for saw the subject that doing the action not commendable. The using of relational model to gave identitythe subject position. In this transformation type, the using of passive, nominalization, and replacement clause aims forobscure or hide the actor generally come from the dominant group or Government.